Evaluation of Interface Shear Strength Coefficient of Alternative Geogrid Made from Para Rubber Sheet - Anubud Liangsunthonsit; Pakkapon Jaroonrat; Jiratchaya Ayawanna; Weerawut Naebpetch; Salisa Chaiyaput (My University, 2023)
In this work, elastic natural rubber compound sheet (RCS) and ribbed smoked sheet grade 3 (RSS) were studied as alternative replacements for polymer geogrid for soil reinforcement. In order to investigate the reinforcing effectiveness in three distinct environments using the interface shear strength coefficient (Rin) by the large-scale direct shear test, the RSS and RCS geogrids were installed independently in sand, lateritic soil, and clay. Using either an RSS geogrid or RCS geogrid, the average Rin is progressively smaller in reinforced sand, lateritic soil, and clay, respectively. Higher tensile strength of reinforced materials using the RCS geogrid than those using the RSS geogrid is encouraged by the better elastic characteristics of the RCS geogrid. Thus, utilizing the RCS geogrid-reinforced materials can better increase the shear strength of coarse-grained soil such as sand and gravel.
Keywords: Geogrid; Direct shear test; Shear Strength; Geotechnical Engineering and Soil Stabilization